Development of nusselt number correlation by wilson plot method combined CFD simulation - Nguyen , Thành Luân; Nguyen , Minh Phú; Nguyen , Minh Hạ (Journal of Technical Education Science, 2021)
The Wilson plot method is a method used to determine the convective heat transfer coefficient in some heat transfer processes. This is a method that has been widely applied in research on heat exchangers, especially for devices with complex and inaccessible heat exchanger surfaces in calculating heat transfer. In this study, the application of the Wilson plot method is presented to develop the Nusselt number correlation of the fluid flow from the CFD simulation results. A model for water heating pipe with the pipe surface with round fins, the outside pipe supplies a constant heat flow were reviewed. The analytical solution for the mathematical model involving energy, linear regression is obtained using an EES (Engineering Equation Solver) program. The research results show that from the CFD simulation data using the Wilson plot method, the Nusselt number correlation of the water flow has been developed with the correlation R2=0,9992. Thereby, it is shown that the Wilson plot method can be used to study heat exchangers in experiments and simulation studies. This method can be applied in teaching experiments or numerical simulations related to heat exchangers for university students.